Corpi e pelle in copertina: bikini, tute spaziali e nuovi modelli di femminile tra cinema e illustrazione (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The transformation in the forms of representation of sexuality has in the swimsuit one of its icons: an emblem of feminine half-nakedness, but also a disturbing exaltation of the female skin. Beach movies reset the impact of this clothing element. Its “space alter ego”, instead, not only enhances the centimeters of exposed skin, but also offers a new body and a new model of femininity. Through looking at comics, magazines and movies, the essay shows that the space suit – often a bikini – is a limit to the carnality of the body as well as a tool for a new identity: a woman aimed to reach a new role.